1943
DOI: 10.1042/bj0370403
|View full text |Cite
|
Sign up to set email alerts
|

The chemical behaviour of dehydro-l-ascorbic acid in vitro and in vivo

Abstract: Vol. 37 PHOSPHORYLASE AND PHOSPHOROLYSIS 403 SUMMARY 1. A modified method for the preparation of phosphorylase by adsorption on A1(OH)3 is described. By this method, phosphorylase can be demonstrated in all animal tissues.2. The phosphorylase activity and the intensity of the glycogen metabolism of a tissue are shown to be positively correlated. The samte is true also of the phosphorolytic breakdown of glycogen. 3. Subcutaneous tissue possesses a highly active phosphorylase, and metabolizes glycogen ati a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

1949
1949
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 4 publications
3
12
0
2
Order By: Relevance
“…BUKIN (5) five minutes at pH 7.0 and 370 C, 30%o of the dehydro-ascorbic acid had hydrolyzed to 2,3-diketo-gulonic acid. PENNY and ZILVA (19,20) reported similar results. values up to 0.5 ml.…”
Section: Results and Discussion Non-enzymatic Reduction Of Dehydro-assupporting
confidence: 75%
“…BUKIN (5) five minutes at pH 7.0 and 370 C, 30%o of the dehydro-ascorbic acid had hydrolyzed to 2,3-diketo-gulonic acid. PENNY and ZILVA (19,20) reported similar results. values up to 0.5 ml.…”
Section: Results and Discussion Non-enzymatic Reduction Of Dehydro-assupporting
confidence: 75%
“…The results of Penney and Zilva (1943), confirmed by the author, show. that diketogulonic acid gives about one-tenth the titre of the equivalent amount of dehydroascorbic acid.…”
Section: Stability Of Dehydroascorbic Acid (A) Effect Of Temperasupporting
confidence: 78%
“…The addition of ten parts per -million of copper (as copper sulphate), which catalyses the atmospheric oxidation of ascorbic acid, had no significant effe( t. Penney and Zilva (1943) have shown that diketogulonic acid is rendered more stable at pH 7.4 by the presence of borate, and the formation of reducing substances on treatment with hydrogen sulphide is thus eliminated. The possibility of using borate in the determination of dehydroascorbic acid was considered, as it would enable dehydroascorbic acid to be removed without giving rise to a residual titre.…”
Section: Investigations On Dehydroascorbic Acid 349mentioning
confidence: 96%
See 2 more Smart Citations